Safety and biodistribution of exosomes derived from human induced pluripotent stem cells - Gu, Zhewei; Yin, Zhiyu; Song, Pengbo; Wu, Ying; He, Ying; Zhu, Maoshu; Wu, Zhengxin; Zhao, Sicheng; Huang, Hongri; Wang, Huihuang; Tong, Cailing; Qi, Zhongquan (Frontiers in Bioengineering and Biotechnology, 2022)
As a new cell-free therapy, exosomes have provided new ideas for the treatment of various diseases. Human induced pluripotent stem cells (hiPSCs) cannot be used in clinical trials because of tumorigenicity, but the exosomes derived from hiPSCs may combine the advantages of iPSC pluripotency and the nanoscale size of exosomes while avoiding tumorigenicity. Currently, the safety and biodistribution of hiPSC-exosomes in vivo are unclear. Here, we investigated the effects of hiPSC-exosomes on hemolysis, DNA damage, and cytotoxicity through cell experiments. We also explored the safety of vein injection of hiPSC-exosomes in rabbits and rats. Differences in organ distribution after nasal administration were compared in normal and Parkinson's disease model mice. This study may provide support for clinical therapy and research of intravenous and nasal administration of hiPSC-exosomes.